استخدام يوتيوب وأثره في تنمية مهارة الكلام: دراسة حالة في مركز اللغة والإعداد الجامعي بالجامعة الإسلامية العالمية بماليزيا - طاهر، فهمي (Kulliyah of Education, International Islamic University Malaysia, 2018)
The purpose of this research is to find out the impact of using YouTube on speech skills at the Centre for Languages and Pre-University Academic Development (CELPAD) at the International Islamic University of Malaysia, a case study. The aim of this research is to evaluate and improve the skill of speech among students who use YouTube in promoting speech skills at CELPAD IIUM. Accordingly, the researcher relied on the descriptive approach to data collection and analysis and adopted this on the experimental approach to know the effect of using YouTube before and after use. The researcher then surveyed the views of the students of CELPAD, which relate to the use of YouTube and the use of research in the form of 85 students. They wre split into an experimental group and control group. A quasi-experimental design was applied in this quantitative study, which consisted of survey, pre-test and post-test protocol. The researcher found that the students showed their approval that YouTube affects the improvement of speech skills and some of them were neutral to their opinion. On the experimental approach, however, the researcher discovered that there was an impact in improving speech skills after using YouTube videos. This fact showed that YouTube is useful in the teaching of language among university students.